Application progress of CRISPR/Cas9 genome-editing technology in edible fungi - Zhang, Yan; Chen, Shutong; Yang, Long; Zhang, Qiang (Frontiers in Microbiology, 2023)
Edible fungi are not only delicious but are also rich in nutritional and medicinal values, thus they are pretty popular among consumers. With the rapid development of the edible fungi industry in the world, especially in China, the cultivation of novel and excellent edible fungi strains is becoming increasingly important. However, conventional breeding methods of edible fungi is laborious and time consuming. CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated nuclease 9) has been a powerful tool for molecular breeding due to its ability to mediate high-efficiency and high-precision genome modification, which has been successfully applied to many kinds of edible fungi. In this review, we briefly summarize the working mechanism of the CRISPR/Cas9 system and highlight the application progress of CRISPR/Cas9 mediated genome editing technology in edible fungi, including Agaricus bisporus, Ganoderma lucidum, Flammulina filiformis, Ustilago maydis, Pleurotus eryngii, Pleurotus ostreatus, Coprinopsis cinerea, Schizophyllum commune, Cordyceps militaris, Shiraia bambusicola. Additionally, we discuss the limitations and challenges encountered using CRISPR/Cas9 technology in edible fungi and provide the potential solutions. Finally, the applications of CRISPR/Cas9 system for molecular breeding of edible fungi in the future is prospected.